Analizator dinamičnega obnašanja koračnih motorjev - Čurkovič, Milan (Ventil (Ljubljana), 2007)
This paper describes the Stepper Motor Dynamics Analyzer. The analyzer is capable of producing several typical characteristics of stepper motors, such as the step response, the static step accuracy, the micro-step accuracy and the dynamics position accuracy. The analyzer can be used in the development and production phases of stepper motors.
Keywords: hitrost; koračni motorji